Structural and electro-magnetic properties of high (BH) max La-Sm substituted Sr-hexaferrite for brushless DC electric motors application - Shekhawat D.; Singh A.K.; Roy P.K. (My University, 2025)
La-Sm substituted Sr-hexaferrite {SrAl 4 (La 0.5 Sm 0.5 ) x Fe 8-x O 19 with x = 0.0, 0.5, 1.0, 1.5} nanomaterials have been synthesized by the auto combustion method. The XRD is supported the magneto-plumbite phase. Rietveld structure reﬁnement is carried out to estimate crystallite size, strain, and variation in lattice parameters with composition. Prepared ferrite grains have a platelet-like shape, and the grain size increases with substitution. Remanence (B r ) magnetization is observed to increase while intrinsic (iH c ) coercivity to decrease with substitution. The dielectric permittivity (ɛ) is found to decrease with the increase in frequency. AC resistivity (ρ) is decreased with the enhancement of La-Sm substitution. The optimized magnetic properties obtained from x = 1.0 composition are B r = 5.19 kG, iH c = 6.18 kOe, (BH) max = 6.69 MGOe, Tc = 492 K, and ρ = 4.30*10 7 Ohm-cm (at 100 kHz). Under 1 kW output power, the ferrite is useful for DC motors application. © 2018 Elsevier B.V.